Retributivism, Penal Censure, and Life Imprisonment without Parole. Issue 1 (2nd January 2019) - Dagan, Netanel; Roberts, Julian V.
Abstract : This article advances a censure-based case against sentences of life imprisonment without the possibility of parole. Our argument justifies a retributive "second look" assessment of long-term prison sentences. The article focuses on the censuring element of long-term prison sentences while reconceptualizing penal censure as a dynamic and responsive concept. By doing so, the article explores the significance of the prisoner's life after sentencing (largely ignored by retributivists) and promotes a more nuanced approach to censure-based proportionality. Policy-makers may welcome this approach as a way to control excessive prison sentences while remaining within a retributive penal framework. Although we are making a general argument about the need for responsive censure within a retributive sentencing regime, the case for this approach is particularly compelling at the present time. Almost all Western nations, and particularly the US, impose very lengthy, often life sentences of imprisonment for a wide range of offences, thereby affecting large numbers of prisoners.